2019
DOI: 10.1039/c8sm01751d
|View full text |Cite
|
Sign up to set email alerts
|

Spherical-cap droplets of a photo-responsive bent liquid crystal dimer

Abstract: Using a photo-responsive dimer exhibiting the transition between nematic (N) and twist-bend nematic (NTB) phases, we prepared spherical cap-shaped droplets on solid substrates exposed to air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…One of the most suitable configurations to observe such a dynamic phenomenon with a structural deformation is a dispersion system of LC droplets in a liquid solvent. The reason for this is the structural diversity: it has been reported that, in LC droplets, the director field was stabilised with various configurations including defects, depending on the anchoring condition at the surface and the anisotropy of the elastic force [36][37][38][39][40][41][42][43][44]. As the motions of the droplets are strongly affected by their structures, it is reasonable that the dynamic phenomena observed in these LC droplets dispersed in a liquid solvent are also various as observed in recent investigations.…”
Section: Introductionmentioning
confidence: 75%
“…One of the most suitable configurations to observe such a dynamic phenomenon with a structural deformation is a dispersion system of LC droplets in a liquid solvent. The reason for this is the structural diversity: it has been reported that, in LC droplets, the director field was stabilised with various configurations including defects, depending on the anchoring condition at the surface and the anisotropy of the elastic force [36][37][38][39][40][41][42][43][44]. As the motions of the droplets are strongly affected by their structures, it is reasonable that the dynamic phenomena observed in these LC droplets dispersed in a liquid solvent are also various as observed in recent investigations.…”
Section: Introductionmentioning
confidence: 75%
“…An example of the macroscopic structure formed by LC has been observed in droplets composed of nematic (N), smectic, or cholesteric (Ch) phase [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Notably, the chiral LC system of the Ch droplets exhibits a wide range of structural diversity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, between the N phase and N TB phase. [46][47][48][49] In order to find liquid crystal dimers with interesting properties, a series of dimers containing a cholesteryl benzoate group were synthesized. These new dimers are denoted with the help of the symbol C-N-DN-x (x = 2, 4, 6, 8, 10, 12, 14), with x denoting the number of carbon atoms of the terminal alkoxy group of azobenzene.…”
Section: Introductionmentioning
confidence: 99%